Phonetic adaptation of germanisms in ХІХ century Belarusian folklore and dialect records - Pakhirka, Veranika U. (Journal of the Belarusian State University. Philology, 2018)
The article considers germanisms in XIX century Belarusian folklore and dialect records. It contains an analysis of the peculiarities of their phonetic adaptation in the Belarusian language according to its vowel-system (akanje, yakanje, transition of sounds [о] and [а] into sounds [y] and [u]) and consonant-system (transition of the sound [f] into sounds [p], [f], [hv]; transition of sounds combination [ch] into sound [k] or [g]; hard [r]; soft [l’]; dissimilation; vocalization of the sound [h] to the sound [g]). When comparing germanisms in Old Belarusian and in XIX century folklore and dialect records, phonetic variability among word forms in different time intervals, as well as differences within the same period are observed which is largely attributed to further phonetic adaptation and folk nature of the analuzed material.
Keywords: folklore and dialect records; phonetic adaptation; vowel system; consonant-system; assimilation; dissimilation